2021
DOI: 10.3389/fimmu.2021.782852
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Responses in Cancer: Boosting Antitumor Immunity Through Activation of Interferon Pathway in the Tumor Microenvironment

Abstract: In recent years, it became apparent that cancers either associated with viral infections or aberrantly expressing endogenous retroviral elements (EREs) are more immunogenic, exhibiting an intense intra-tumor immune cell infiltration characterized by a robust cytolytic apparatus. On the other hand, epigenetic regulation of EREs is crucial to maintain steady-state conditions and cell homeostasis. In line with this, epigenetic disruptions within steady-state cells can lead to cancer development and trigger the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 233 publications
0
16
0
Order By: Relevance
“…The IFN-1 immune response mediated by dsRNA induction of multiple upregulated HERV transcripts has been identified as a critical anticancer mechanism of demethylation ( Chiappinelli et al, 2017 ). This stimulation that generated bidirectional HERV transcripts formed dsRNA detectable by cellular PRRs, and caused type I and type III IFN responses in colorectal cancer cells, reducing the antitumor activity of DNA methyltransferase inhibitors ( Vitiello et al, 2021 ). These dsRNAs can be assumed to be PAMPs for human PRR, stimulating innate immune responses through the TLR3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-1 immune response mediated by dsRNA induction of multiple upregulated HERV transcripts has been identified as a critical anticancer mechanism of demethylation ( Chiappinelli et al, 2017 ). This stimulation that generated bidirectional HERV transcripts formed dsRNA detectable by cellular PRRs, and caused type I and type III IFN responses in colorectal cancer cells, reducing the antitumor activity of DNA methyltransferase inhibitors ( Vitiello et al, 2021 ). These dsRNAs can be assumed to be PAMPs for human PRR, stimulating innate immune responses through the TLR3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that viral infection may enhance anti-tumor immunity in cancer patients by activating type-I interferon signaling [89][90][91]. To estimate the effect of viral load on tumor immune infiltration, we compared tumor expression of immune cell transcriptional signatures (TS) [61,62] between 88 HPV-infected and 412 HPV-free tumors in 500 primary HNSCC tumor biopsies (Figure 1B).…”
Section: Hpv-infected Hnscc Patients Have Increased Immune Cell Ts Ex...mentioning
confidence: 99%
“…Thus, HERVs are targeted as a promising internal strategy to enhance the anti-tumor immune responses by sensitizing tumor cells for immunotherapies. Vitiello et al (2021) reviewed the role of HERVs activation as a promising molecular predictive marker and immunotherapy target in cancers.…”
Section: Human Endogenous Retroviruses In Carcinogenesismentioning
confidence: 99%